Analysis of the Determinants of Chinese FDI in Laos - Phommouny, Phetsamone; He, Shuquan (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Foreign Direct Investment (FDI) plays a crucial role in promoting long-term economic growth and development for both host and source nations. Over the past thirty years, Laos has experienced a significant increase in FDI inflows, particularly from China. This paper examines the determinants of Chinese FDI inflows in Laos. The paper employs Ordinary Least Squares (OLS) Regression and Stata 21 to analyze the time series data from 2000-2020, which consists of 21 observations. The findings demonstrate that the ample natural resources and market size of Laos have a substantial and favorable influence on the flow of Chinese FDI into Laos. Furthermore, the presence of bilateral trade between Laos and China, the level of infrastructure in Laos, and the exchange rate in Laos all have a favorable influence on Chinese FDI inflows to Laos. In this context, this research enhances the current body of knowledge on the factors that drive Chinese foreign direct investment in developing nations, especially in Laos. In addition, the findings of this study will enhance the current knowledge regarding the determinants of Chinese FDI abroad by providing support for the common argument that Chinese FDI is driven by resource-seeking and market-seeking motives.